The place of al was cared by ahmad's ibn in the arab linguistics - Atabay, B. A.; Al Huli, A. (Journal of Oriental Studies, 2016)
The work of an outstanding expert on Arabic linguistics century Al-Khalil ibn Ahmad is considered in this article. "Kitab al-ain" Dictionary and al-Khalil ibn Ahmad‘s tractate "Kitab al-arud" have always been recognized by expert on Arab studies. Scientists have proven that al-Khalil ibn Ahmad had other writings such as "Kitab al-nagm", "Kitab al -iqa‘,"Al-Manzuma fi an- nahu"."The first two books are similar in content to "Kitab al-arud." An articulate grammatical term system was developed in the tractates"Al-Manzuma fi an- Nahu". It is available in the "Kitab al-ain” tractate.